2017
DOI: 10.5455/ijlr.20170615051642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Genetic Factors on Production and Reproduction Traits in Deoni Cattle

Abstract: The present investigation was carried out in Deoni cattle maintained at cattle breeding farm, College of Veterinary and Animal Sciences, Udgir Dist-Latur to see the influence of various non-genetic factors on production and reproduction traits. The breeding tract of Deoni breed is the 714.26±69.72 litres, 214.52±43.25 days, 204.77±32.86 days, 489.23±36.83 days, 284.89±31.92 days and 288.83±10.29 days, respectively. Service period had highly significant (p<0.01)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
2
8
0
Order By: Relevance
“…In Table1result revealed that TMY of Kankrej cows was not differ significantly with each other. Table1) in primiparous Kankrej cow and it is in close agreement withDongre et al (2017) andParmar et al (2019) for Deoni cattle and crossbred cattle, respectively. These findings are not in agreement ofNarwaria et al (2017) for Sahiwal cattle.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In Table1result revealed that TMY of Kankrej cows was not differ significantly with each other. Table1) in primiparous Kankrej cow and it is in close agreement withDongre et al (2017) andParmar et al (2019) for Deoni cattle and crossbred cattle, respectively. These findings are not in agreement ofNarwaria et al (2017) for Sahiwal cattle.…”
supporting
confidence: 90%
“…These findings are in close association with the reports of Al-samarai et al (2015) as 298.28 days for Holstein 1). These findings are supported by the Bhutkar et al (2014); Kumar et al (2014); Dongre et al (2017) and Parmar et al (2018). They reported that period of calving did not have any effect on LL.…”
Section: Lactation Length (Ll)supporting
confidence: 54%
“…higher LMY was there than in summer season. Dongre et al (2017) reported non-significant (p > .05) effect of total LMY with season of calving, period of calving and parity whereas highest MY was observed during summer season and fourth and onward parities. Bhutkar et al (2014) reported non-significant association of season of calving with all the production traits like LMY, PY and lactation period.…”
Section: Phenotypic Correlations Among Traitsmentioning
confidence: 86%
“…Dongre et al. (2017) reported non‐significant ( p > .05) effect of total LMY with season of calving, period of calving and parity whereas highest MY was observed during summer season and fourth and onward parities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation